2015
DOI: 10.1016/j.clgc.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II Trial of Paclitaxel With Ifosfamide Followed by High-Dose Paclitaxel, Ifosfamide, and Carboplatin (TI-TIC) With Autologous Stem Cell Reinfusion for Salvage Treatment of Germ Cell Tumors

Abstract: Purpose Salvage high-dose chemotherapy with autologous stem cell transplant (ASCT), consisting of 2–3 sequential cycles of high-dose (HD) carboplatin and etoposide (CE) can achieve durable remissions in approximately one-half of relapsed germ cell tumor patients. To improve upon these results and based on success with paclitaxel, ifosfamide, and cisplatin (TIP) as salvage conventional-dose chemotherapy, we conducted a phase I/II trial of HD paclitaxel plus ifosfamide (TI), substituting carboplatin for cisplati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The TI-CE regimen consists of paclitaxel and ifosfamide induction for up to 2 cycles followed by high-dose carboplatin and etoposide with autologous SCT every 21–28 days for 3 cycles. The efficacy of this approach was demonstrated in a phase I/II trial that reported a 47% 5-year disease-free survival and 52% overall survival [40]. The TIGER trial (NCT02375204 at www.clinicaltrials.gov) is an ongoing multicenter, open-label phase III study comparing second-line TI-CE vs TIP in patients with relapsed or refractory GCTs.…”
Section: Salvage Therapy For Refractory or Recurrent Gctsmentioning
confidence: 99%
“…The TI-CE regimen consists of paclitaxel and ifosfamide induction for up to 2 cycles followed by high-dose carboplatin and etoposide with autologous SCT every 21–28 days for 3 cycles. The efficacy of this approach was demonstrated in a phase I/II trial that reported a 47% 5-year disease-free survival and 52% overall survival [40]. The TIGER trial (NCT02375204 at www.clinicaltrials.gov) is an ongoing multicenter, open-label phase III study comparing second-line TI-CE vs TIP in patients with relapsed or refractory GCTs.…”
Section: Salvage Therapy For Refractory or Recurrent Gctsmentioning
confidence: 99%
“…Patients were treated with TI-CE on a clinical trial, [9][10][11] TI-CE as standard of care, or TI followed by high-dose paclitaxel, ifosfamide, and carboplatin (TI-TIC) on a clinical trial. 19 For the TI-CE program, one or two cycles of TI with mesna were given 14 days apart (Cycles 1 and 2) followed by three cycles of high-dose CE with autologous stem cell support every 21-28 days (Cycles 3-5; Table S1). Carboplatin dosing was by target area under the curve (AUC) and varied during phase 1 of the TI-CE clinical trial.…”
Section: Introductionmentioning
confidence: 99%